Theme of Laughter in Ksenia Buksha's Advent - Kapitalina V. Sinegubova (СибСкрипт, 2023)
This article discusses laughter as one of the structure-forming themes in Ksenia Buksha's novel Advent (2021). The novel consists of two parts, the retrospective one being graphically separated from the main narrative. The theme of laughter does not seem to be connected with the event part; however, it brings about several sidelines. Methodologically, the research relied on the theory of motif developed by I. V. Silantiev, where the motif is considered as part of the narrative. The variability of laughter in literature is complemented by its multifaceted character in philosophy and culture. The works by S. S. Averintsev, L. V. Karasev, and M. T. Ryumina made it possible to understand the semantics of laughter as a cultural and social phenomenon. In her novel, K. Buksha hardly ever links laughter with the category of comic: in fact, laughter almost never accompanies mockery. As a rule, laughter in Advent is involuntary and unmotivated. It is associated with the true, imaginary, or impossible liberation of the characters from eternal routine and malign infinity, be it their entire lives or just a depressing episode. The laughter moments belong both to the main and episodic characters, which indicates that laughter is a universal symbol of crisis. This interpretation contributes to a deeper philosophical and ontological understanding of the contemporary Russian literature.